STUDENTS' PERCEPTION OF ZOTERO UTILIZATION IN REFERENCE SETTING IN THE ACADEMIC TEXT WRITING PROCESS IN HIGHER EDUCATION - Rafi'i, Muhammad; Amir, Amriani; Mariyadi, Mariyadi (JURNAL EDUSCIENCE, 2025)
Purpose – Zotero is a Reference Management Software (RMS) that can help students manage references, citations, and bibliographies automatically. However, the background factors and the extent to which students understand and feel the benefits of using Zotero in this process have not been widely studied, especially from a qualitative research perspective. Therefore, this study aims to examine the factors behind using Zotero as a reference management tool and its impact on the process of writing academic texts for students.Methodology – The research employs a qualitative design with data collected from twelve undergraduate students at Tanjungpura University during the 2023-2024 academic year. Participants were selected based on their confirmed experience using Zotero for academic writing. Data collection was conducted through semi-structured interviews, and thematic analysis was applied to identify patterns and themes in the responses.Findings – The research findings indicate three main themes. The first theme is the perception of ease of use, with subthemes of ease of download, installation, and use, as well as ease of understanding and learning. The second theme is the perception of usefulness with the subthemes of time efficiency, improved score, improving writing quality, ease of citation, and bibliography, making it easy to translate. The third theme is the influence of using the subthemes of academic encouragement, friend encouragement, and lecturer encouragement. These findings underscore Zotero’s effectiveness in supporting students’ academic writing needs.Significance – This research benefits educators, students, and academic institutions seeking to incorporate practical reference management tools into academic writing practices. It highlights Zotero's potential to streamline the writing process and improve academic outcomes, offering valuable insights for integrating technology into higher education curricula. Keywords : Zotero, RMS, Reference Management, Student, Perception